Emerging tools to advance neuroethology in butterflies and moths - Francesco Cicconardi; Max S. Farnworth; Robin Grob; Donya N. Shodja; Caroline N. Bacquet; Basil el Jundi; Arnaud Martin; Stephen H. Montgomery (Journal of Comparative Physiology A, 2026)
Butterflies and moths have played historically important roles in developing our understanding of both ecology and evolutionary biology, and neuroethology. In both contexts, the diversity of behavioral strategies and specializations displayed by different Lepidoptera make them informative case studies. However, as in neuroscience more broadly, lepidopteran neuroethology has tended to focus on intricate functional studies within a small number of the most tractable species. In contrast, ecologists and evolutionary biologists have often taken a broader view, using phylogenetic and comparative approaches to extract general patterns of diversification, and to exploit the diversity of butterflies and moths to understand general evolutionary processes. Uniting these approaches and traditions has been restricted, largely due to technical challenges of working with unestablished study systems and a lack of resources beyond basic tools. Now, however, the prospects for broader comparative studies of the neural basis of behavior within a phylogenetic and/or ecological framework are increasingly positive. This is in large part due to the emergence of new molecular sequencing approaches and associated tools. These allow for the survey of cell types, the spatial location of their soma, development of new cell-type markers for targeted analyses, and quantification of the dynamic regulation of gene expression at a tissue or cell specific level. Results of these molecular methods can be combined with technical developments in free flying behavioral experiments in tethered animals that permit neural recordings of natural behavior, and functional genetics tools that can allow for more precise manipulation of these behaviors or the neural structures that support them. Here, we review these new approaches, their potential application, and discuss how we can use them to advance the development of new, integrative systems for studying the neural basis of behavior in butterflies and moths.

The diversity of lepidopteran spatial orientation strategies – neuronal mechanisms and emerging challenges in a changing world - Robin Grob; Max S. Farnworth; Jacqueline Degen; Eric Warrant; Stephen H. Montgomery; Basil el Jundi (Journal of Comparative Physiology A, 2026)
The Lepidoptera, butterflies and moths, display an astonishing diversity of spatial orientation strategies essential for survival, reproduction, and ecological success. These spatial orientation strategies range from basic taxes to light, wind, gravity, and chemical cues, to more advanced strategies such as straight-line dispersal, multigenerational migration across continents, and complex trap-lining foraging involving long-term spatial memory. These orientation behaviours are tightly integrated with the ecological roles of lepidopterans as pollinators, prey, and bioindicators, and are supported by a flexible neuronal network. Of special interest for successful orientation are higher-order integration centres like the mushroom bodies (centres for learning and memory) and the central complex (the centre for spatial orientation and locomotion). These centres support cue integration, compass orientation, memory, and directional decision-making. However, anthropogenic stressors, including habitat fragmentation, light pollution, pesticides, and electromagnetic noise, threaten both the environmental cues and the neural systems facilitating lepidopteran navigation, with potential cascading effects on biodiversity and ecosystem health. By combining insights from behavioural ecology, neurobiology, and conservation, we aim to provide a comprehensive overview of the challenges and adaptations that shape the navigational toolkit of lepidopterans, underlining their significance as animal models for studying spatial orientation in a changing world.

The role of learning-walk related multisensory experience in rewiring visual circuits in the desert ant brain - Wolfgang Rössler; Robin Grob; Pauline N. Fleischmann (Journal of Comparative Physiology A, 2023)
Efficient spatial orientation in the natural environment is crucial for the survival of most animal species. Cataglyphis desert ants possess excellent navigational skills. After far-ranging foraging excursions, the ants return to their inconspicuous nest entrance using celestial and panoramic cues. This review focuses on the question about how naïve ants acquire the necessary spatial information and adjust their visual compass systems. Naïve ants perform structured learning walks during their transition from the dark nest interior to foraging under bright sunlight. During initial learning walks, the ants perform rotational movements with nest-directed views using the earth’s magnetic field as an earthbound compass reference. Experimental manipulations demonstrate that specific sky compass cues trigger structural neuronal plasticity in visual circuits to integration centers in the central complex and mushroom bodies. During learning walks, rotation of the sky-polarization pattern is required for an increase in volume and synaptic complexes in both integration centers. In contrast, passive light exposure triggers light-spectrum (especially UV light) dependent changes in synaptic complexes upstream of the central complex. We discuss a multisensory circuit model in the ant brain for pathways mediating structural neuroplasticity at different levels following passive light exposure and multisensory experience during the performance of learning walks.

Magnetosensation during re-learning walks in desert ants (Cataglyphis nodus) - Pauline N. Fleischmann; Robin Grob; Wolfgang Rössler (Journal of Comparative Physiology A, 2022)
At the beginning of their foraging careers, Cataglyphis desert ants calibrate their compass systems and learn the visual panorama surrounding the nest entrance. For that, they perform well-structured initial learning walks. During rotational body movements (pirouettes), naïve ants (novices) gaze back to the nest entrance to memorize their way back to the nest. To align their gaze directions, they rely on the geomagnetic field as a compass cue. In contrast, experienced ants (foragers) use celestial compass cues for path integration during food search. If the panorama at the nest entrance is changed, foragers perform re-learning walks prior to heading out on new foraging excursions. Here, we show that initial learning walks and re-learning walks are structurally different. During re-learning walks, foragers circle around the nest entrance before leaving the nest area to search for food. During pirouettes, they do not gaze back to the nest entrance. In addition, foragers do not use the magnetic field as a compass cue to align their gaze directions during re-learning walk pirouettes. Nevertheless, magnetic alterations during re-learning walks under manipulated panoramic conditions induce changes in nest-directed views indicating that foragers are still magnetosensitive in a cue conflict situation.